Prevalence and Psychosocial Correlates of Mental Health Outcomes Among Chinese College Students During the Coronavirus Disease (COVID-19) Pandemic - Chi, Xinli; Becker, Benjamin; Yu, Qian; Willeit, Peter; Jiao, Can; Huang, Liuyue; Hossain, M. Mahhub; Grabovac, Igor; Yeung, Albert; Lin, Jingyuan; Veronese, Nicola; Wang, Jian; et al. (Frontiers in Psychiatry, 2020)
Objectives: To investigate the prevalence and risk factors for poor mental health Chinese university students during the COVID-19 pandemic. Method: Chinese nation-wide on-line cross-sectional survey on university students, collected between February 12th and 17th, 2020. Primary outcome was prevalence of clinically-relevant post traumatic stress disorders symptoms. Secondary outcomes on poor mental health included prevalence of clinically-relevant anxiety and depressive symptoms, while post traumatic growth was considered as indicator of effective coping reaction. Results: Of 2,500 invited Chinese university students, 2,038 completed the survey. Prevalence of clinically-relevant PTSD, anxiety and depressive, symptoms, and PTG were 30.8%, 15.5%, 23.3%, and 66.9% respectively. Older age, knowing people who had been isolated, more ACEs, higher level of anxious attachment, and lower level of resilience all predicted primary outcome (all p < 0.01). Conclusions: A significant proportion of young adults exhibit clinically relevant PTSD, anxious or depressive symptoms, but a larger portion of individuals showed to effectively cope with COVID-19 pandemic. Interventions promoting resilience should be provided, even remotely, to those subjects with specific risk factors to develop poor mental health during COVID-19 or other pandemics with social isolation.